Hubungan Media Audio Visual dengan Hasil Belajar Siswa pada Materi Teks Puisi - Bambang Irawan; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The purpose of this study was to determine the relationship between the use of audio-visual learning media and student learning outcomes in identifying the elements of poetry text building in class VIII SMP Al-Azhar Syifa Budi Pekanbaru. This research is a quantitative research with correlational method. After taking data on 67 samples and analyzing the collected data, the results of the correlation coefficient between variable X and variable Y are 0.627 (positively correlated) which shows a strong correlation level, which is in the range of 0.60 - 0.799. In addition to being positively correlated, the results of the analysis prove a significant relationship with the tcount value of 6.484 > ttable 1.66864 (at the 5% significance level with dk 65) which means rejecting Ho, which is significant. The significant test was strengthened by looking at the value of Sig. that is, 0.00 is smaller than 0.05 (0.00 < 0.05), which means that there is a positive and significant relationship between variable X and variable Y. Furthermore, the magnitude of the coefficient of determination is 0.3844, meaning that the contribution of variable X to variable Y is equal to 39.31% and 60.69% were determined by other factors, such as learning motivation, mastery of learning methods for teachers, school discipline, student internal factors, environment, and others. Based on the results of the analysis that has been carried out, it can be concluded that the use of audio-visual learning media has a positive and significant relationship to student learning outcomes in the matter of identifying the elements of poetry text building in class VIII SMP Al-Azhar Syifa Budi Pekanbaru.